Partial Substitution of Maize for Sorghum With or Without Supplemental Hydrolysable Tannins on Digestibility and Postprandial Glycemia in Adult Dogs - Teixeira, Liege; Pinto, Caroline Fredrich Dourado; Machado, Geruza Silveira; Kessler, Alexandre de Mello; Trevizan, Luciano (Frontiers in Veterinary Science, 2021)
The effect of partial substitution of maize for sorghum, containing condensed tannins (CT), with or without the addition of a purified hydrolysable tannin extract (HT) on dog apparent digestibility and glycemic response were evaluated. The trial was conducted with eight adult dogs distributed in four treatments: (M) 50% maize; (MS) 25% maize + 25% sorghum; (MHT) 50% maize + 0.10% HT; (MSHT) 25% maize + 25% sorghum + 0.10% HT; in a balanced incomplete Latin square design in three periods, with two dogs per diet, per period. Data were analyzed by ANOVA procedure and glycemic response by repeated measures ANOVA over time (P < 0.05). The phenolic compounds analyzed were not detected after extrusion process, with a reduction mainly in diets containing sorghum. There were no differences in the digestibility coefficients of nutrients and energy between the dietary treatments (P > 0.05). Fecal and urinary characteristics were not changed by the addition of sorghum and HT (P > 0.05). The fecal score remained within the ideal classification as hard, dry, firm stools. A moderate increase in fecal pH was observed on dogs fed diets containing sorghum (P = 0.0948). Additionally, the partial replacement of maize for sorghum associated or not with HT do not alter the glycemic aspects evaluated among dietary treatments (P > 0.05). Availability of nutrients from maize and sorghum were similar. Tannins did not interfere in the nutritional capacity of the ingredients.